Herd management and breeding practices of sheep owners in a mixed crop-livestock and a pastoral system of Ethiopia - Getachew, T.; Haile, Aynalem; Tibbo, Markos; Sharma, A.K.; Sölkner, Johann; Wurzinger, Maria (2010)
An exploratory survey was undertaken to understand sheep production system, breeding practices and selection criteria for Ethiopian Menz and Afar sheep breeds in their home tract as a step towards developing sustainable sheep breeding strategies. The mean sheep flock size was 31.6 in Menz and 23.0 in Afar area. Half of the pastoralists (Afar) and one-fifth of smallholder farmers (Menz) do not have a breeding ram. Mating was predominantly uncontrolled. Higher chance of mixing sheep flocks was reported in most of the seasons. Menz and Afar rams were castrated at 1.7 and 1.5 years old, respectively. Castrates were kept for longer period of time, on average for 1.9 years in Menz and 3.1 years in Afar. Appearance/conformation was the most important trait in choosing a breeding ram for both Menz and Afar sheep owners. Breeding ewes are chosen based on lambing interval and mothering ability in both crop-livestock and pastoral systems; and milk yield in pastoral system. Afar ewes produce mean daily milk yield of 224 ml. In Menz area sheep are kept for income, meat, manure, coarse wool and as means of saving, in that order. In Afar area, sheep are kept for milk, meat and income. Livestock improvement programs targeting smallholder farmers need to incorporate existing traditional herding and breeding practices, trait preferences and the multiple roles of sheep.